Design and Development of a Wireless Energy Meter with Automatic Cos phi Corrector Feature Based on Internet of Things - Irsyadi, Fakih; Hastomo, Rafifnanda; Suhono (Universitas Muhammadiyah Surakarta, 2024)
The increasing need for energy efficiency and more accurate monitoring of energy consumption has driven the development of intelligent energy metering systems. This Final Project discusses the development of Wireless Energy Meter that integrates sensor technology and data analysis for better monitoring and prediction of energy consumption. The main objective of this research is to improve understanding of household energy consumption patterns and develop power factor improvement algorithms that can provide better use of energy efficiency in the future. At the first stage, the system is implemented using energy sensors connected to the household electrical network. The data obtained from this sensor is sent to the Thingspeak application for later monitoring. The second stage involves developing an algorithm to automatically correct the power factor that the capacitor will later embed to correct cos phi if the existing power factor is less than a predetermined set point. The results of this study show that the system that has been developed is able to provide real-time monitoring of energy consumption and improve electricity quality for better energy efficiency in the future. This can help users to be more efficient in energy use, identify potential savings, and reduce environmental impact. In addition, this system can be used by equipment in households whose purpose is to optimize the use of daily electricity loads.